Effective Excess Charge Density in Water Saturated Porous Media - Duy Thanh, Luong (VNU Journal of Science: Mathematics - Physics; Vol 34 No 4DO - 10.25073/2588-1124/vnumap.4294, 2018)
A model for the effective excess charge in a capillary as well as in porous media is developed for arbitrary pore scales. The prediction of the model is then compared with another published model that is limited for a thin electric double layer (EDL) assumption. The comparison shows that there is a deviation between two models depending on the ratio of capillary/pore radius and the Debye length. The reasons for the deviation between two models are not only due to the thin EDL assumption to get electrical potential and charge distribution in pores but also to some other approximations for integral evaluations. The results suggest that the model developed in this work can be used with arbitrary capillary/pore scale and thus is not restricted to the thin EDL assumption. Keywords: Zeta potential, porous media, electric double layer, effective excess charge. References [1] M. Aubert, Q.Y. Atangana, Groundwater, 34 (1996) 1010–1016. [2] A. Finizola, J.-F. Lénat, O. Macedo, D. Ramos, J.-C. Thouret, F. Sortino, J. Volcanol. Geoth. Res., 135 (2004) 343–360. [3] C. Doussan, L. Jouniaux, J.-L. Thony, Journal of Hydrology 267 (2002) 173–185. [4] F. Perrier, M. Trique, B. Lorne, J.-P. Avouac, S. Hautot, P. Tarits, Geophys. Res. Lett. 25 (1998) 1955–1958. [5] Martinez-Pagan, P., A. Jardani, A. Revil, and A. Haas, Geophysics 75 (2010) WA17–WA25. [6] Naudet, V., A. Revil, J.-Y. Bottero, and P. Bgassat, Geophysical Research Letters 30 (2003). [7] V. Naudet, M. Lazzari, A. Perrone, A. Loperte, S. Piscitelli, V. Lapenna, Engineering Geology 98 (2008) 156-167. [8] A. Perrone, A. Iannuzzi, V. Lapenna, P. Lorenzo, S. Piscitelli, E. Rizzo, F. Sdao, Journal of Applied Geophysics 56 (2004) 17-29. [9] Jouniaux, L., A. Maineult, V. Naudet, M. Pessel, and P. Sailhac, C. R. Geoscience 341 (2009). [10] Revil, A., and A. Jardani, The Self-Potential Method: Theory and Applications in Environmental Geosciences, Cambridge University Press, 2013. [11] Hunter, R., Zeta Potential in Colloid Science: Principles and Applications, Colloid Science Series, Academic Press, 1981. [12] Leroy, P., and A. Revil, Journal of Colloid and Interface Science, 270 (2004) 371–380. [13] T. Ishido, H. Mizutani, Journal of Geophysical Research 86 (1981) 1763-1775. [14] P. W. J. Glover, E. Walker, M. Jackson, Geophysics 77 (2012) D17–D43. [15] Revil, A., and P. Leroy, Journal of Geophysical Research 109 (2004). [16] Linde, N., D. Jougnot, A. Revil, S. K. Matthäi, T. Arora, D. Renard, and C. Doussan, Geophys. Res. Lett. 34 (2007) L03306. [17] Revil A. and Mahardika H, Water Resources Research 49 (2013) 744–766. [18] Jardani, A., A. Revil, A. Bolève, A. Crespy, J. Dupont, W. Barrash and B. Malama, Geophysical Research Letters, 34 (2007) L24,403. [19] L. Guarracino, D. Jougnot, Journal of Geophysical Research - Solid Earth 123 (2018) 52-65. [20] Jackson M.D., Leinov E., International Journal of Geophysics 2012 (2012). [21] Gierst L., J. Am. Chem. Soc. 88 (1966) 4768. [22] Rice, C., and R. Whitehead, J. Phys. Chem. 69 (1965) 4017–4024. [23] Pride, S., Physical Review B 50 (1994) 15,678–15,696. [24] Bear, J., Dynamics of Fluids in Porous Media, Dover Publications, New York, 1988. [25] Chan I. Chung, Extrusion of Polymers: Theory & Practice, Hanser-2nd edition, 2010. [26] J. Vinogradov, M. Z. Jaafar, M. D. Jackson, Journal of Geophysical Research 115 (2010).